MgN: a new promising material for spintronic applications - Sanvito, Stefano; Droghetti, Andrea (My University, 2009)
We present rocksalt MgN as a d 0 magnet with potential for spintronics applications. Our density-functional theory calculations demonstrate that rocksalt MgN is at the verge of half-metallicity, with an electronic struc- ture robust against the choice of exchange and correlation functional. Furthermore the calculated heat of formation describes the compound as metastable and suggests that it can be fabricated by tuning the relative Mg and N abundance during growth. Intriguingly the equilibrium lattice constant is close to that of MgO so that MgN is likely to form as an inclusion during the fabrication of N-doped MgO. If MgN can be made, the MgO/MgN system may become a materials platform for magnetic tunnel junctions not incorporating any transition metals
PUBLISHED
Keywords: Physics; Nanoscience & Materials